Deterioration Characteristics of Cement-Limestone Powder Paste Under Compound Erosion Solution - Shuhua LIU; Lu WANG; Ningning HU; Junwei SONG (Medžiagotyra, 2018)
The deterioration characteristics of cement-limestone powder paste under compound erosion solution were studied in this paper by determining the compressive and flexural strength of pastes, the hydration products and SEM micrographs. The results indicate that H+ and SO42- ions play major roles in compound erosion solution. Besides the neutralization reaction between H+ ions and Ca(OH)2, the reaction between Ca2+ ions and SO42- ions generates CaSO4·2H2O and results in expansion. The crystal hydration products of all pastes before erosion are Ca(OH)2 and some CaCO3 from unhydrated limestone powder. While after erosion, the content of CaCO3 and Ca(OH)2 decreases rapidly and more gypsum forms. Limestone powder may improve the resistance to compound erosion sometimes. The resistance to compound erosion solution of compressive strength becomes weaker with the increase of the dosage of limestone powder (LP), while that of flexural strength becomes stronger. The compound erosion resistance is strong for the pastes with fly ash (FA) and LP, which can accelerate the compressive and flexural strength over curing age. DOI: http://dx.doi.org/10.5755/j01.ms.24.2.17644